2021
DOI: 10.1111/inm.12864
|View full text |Cite
|
Sign up to set email alerts
|

Family expectations of inpatient mental health services for adults with suicidal ideation: a qualitative study

Abstract: Involvement of family members of adults with suicidal ideation is a key area of improvement in inpatient mental health services. To support family involvement in this context, it is crucial to understand what care and treatment family members expect for their relative. This qualitative study based on grounded theory involved interviews with 14 family members, including partners, parents, adult children and siblings. The family members' expectations of care and treatment in inpatient mental health services were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(48 citation statements)
references
References 45 publications
(137 reference statements)
0
46
0
2
Order By: Relevance
“…The way of recruiting participants was in line with positive experiences from previous research by Vandewalle et al . (2021a, 2021b).…”
Section: Methodsmentioning
confidence: 99%
“…The way of recruiting participants was in line with positive experiences from previous research by Vandewalle et al . (2021a, 2021b).…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted in Ghana (Asare-Doku et al, 2017) identified social support as a coping resource for mothers, but not fathers, interpreted by the author as evidence of gendered responses to suicidal behaviour within the family. Some carers had sought professional emotional support, primarily in the form of individual counselling (Garcia-Williams & McGee, 2016;Nosek, 2008;Nygaard et al, 2019;Vandewalle et al, 2021;Wolk-Wasserman, 1987a) while others identified personal professional emotional support as an unresolved support need (Dransart & Guerry, 2017;Inscoe et al, 2021;Ngwane & van Der Wath, 2019;Wolk-Wasserman, 1987b).…”
Section: Descriptive Theme 12: Coping Alongside Suicide Riskmentioning
confidence: 99%
“…Indeed, regarding hospital admission, one carer noted: 'I am always restless and anxious, at home, at work… and then his admission created a moment of rest, to take some time off for myself. Because I knew: they will take care of him' (Vandewalle et al, 2021(Vandewalle et al, , p. 1142.…”
Section: Descriptive Theme Sharing the Responsibility Of Carementioning
confidence: 99%
See 2 more Smart Citations